Reliability and validity of a General Nutrition Knowledge Questionnaire for adults in a Romanian population - Putnoky, Salomeia (Eur J Clin Nutr, 2020)
BACKGROUND: Nutritional knowledge assessment is an important component in nutrition research, and a prerequisite for the implementation of many policies and programs aimed at improving eating behavior. In order to generate objective results, validated tools for a given population must be employed. The aim of this study was to determine the validity and reliability of a nutrition knowledge questionnaire for Romanian adults. METHODS: Kleimann’s version of a General Nutrition Knowledge Questionnaire, was translated and adapted to Romanian language, culture, and cuisine. The final format was developed in several steps and used four components: internal and external reliability were assessed in a general population sample (n1 = 412), respectively in a subgroup (n2 = 46) from Component 1; Component 3 assessed construct validity (n3 = 96) using the “known-groups” method; Component 4 (convergent validity, n4 = 508) tested the association between socio-demographic characteristics and nutrition knowledge. RESULTS: The overall internal reliability was 0.878 and the external reliability was >0.880 in all sections, and overall. Specialists had higher scores than nonspecialists, with a very large effect size. In the general population, females scored higher than males, and middle-aged and older adults scored higher than young adults. Higher scores were associated with higher levels of education. The characteristics of individuals prone to giving wrong answers were: males (beta = 0.170), high school or less (beta = 0.167), and no training in nutrition (beta = 0.154). CONCLUSIONS: The Romanian version of the General Nutrition Knowledge Questionnaire is a reliable and valid tool for measuring nutrition knowledge in adults.